Theological formation for Christian missions : a festschrift for Ian Walter Payne - George, Roji Thomas; John, Aruthuckal Varughese; Vedhamanickam, Prabhu Singh (Bengaluru, India. SAIACS Press., 2019)
As an educator committed to theological formation for Christian missions, Ian W. Payne served SAIACS for many years, the final ten years of which he served as the principal of the college. As an appreciation of his labor of love for the church in India through SAIACS, this festschrift presents a collection of articles that cover Payne's broad interest in theology, pedagogy, and Christian missions from his friends and former colleagues.
Keywords: Festschrift; Missions.-- Theory; Ian Walter Payne.-- SAIACS; Missions.-- India, South; Christian Theology.-- India; Christian education.-- Bengaluru, South India; Contributed articles